Combination rhIL-15 and Anti-PD-L1 (Avelumab) Enhances HIVGag-Specific CD8 T-Cell Function. (20th May 2020) - Goshu, Bruktawit A; Chen, Hui; Moussa, Maha; Cheng, Jie; Catalfamo, Marta
Abstract: In chronic HIV infection, virus-specific cytotoxic CD8 T cells showed expression of checkpoint receptors and impaired function. Therefore, restoration of CD8 T-cell function is critical in cure strategies. Here, we show that in vitro blockade of programmed cell death ligand 1 (PD-L1) by an anti-PD-L1 antibody (avelumab) in combination with recombinant human interleukin-15 (rhIL-15) synergistically enhanced cytokine secretion by proliferating HIVGag-specific CD8 T cells. In addition, these CD8 T cells have a CXCR3 + PD1 −/low phenotype, suggesting a potential to traffic into peripheral tissues. In vitro, proliferating CD8 T cells express PD-L1 suggesting that anti-PD-L1 treatment also targets virus-specific CD8 T cells. Together, these data indicate that rhIL-15/avelumab combination therapy could be a useful strategy to enhance CD8 T-cell function in cure strategies. Abstract : In vitro PD-L1 (avelumab) in combination with rhIL-15 synergistically enhanced cytokine secretion by proliferating HIVGag-specific CD8 T cells with a CXCR3 + PD1 −/low phenotype. In addition, avelumab targeted PD-L1 + proliferating HIVGag-specific CD8 T cells.